2014
DOI: 10.1111/hsc.12098
|View full text |Cite
|
Sign up to set email alerts
|

The healthcare experiences of Koreans living in North Carolina: a mixed methods study

Abstract: This study examined the healthcare experiences of Korean immigrants aged 40-64 living in the North Carolina Triangle area of the Southeastern United States. Using a mixed methods design, we collected quantitative data via a questionnaire from 125 participants and conducted a focus group with 10 interviewees from December 2010 to February 2011. The quantitative data were analysed using t-tests and chi-square tests, and a thematic analysis was used for the focus group study. Questionnaire findings showed that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Previous studies on Korean immigrants living in North Carolina, USA, suggested that their socioeconomic status (e.g. education, income) affects their health more than other factors (De Gagne et al, 2014;De Gagne, Oh, So, Haidermota, & Lee, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on Korean immigrants living in North Carolina, USA, suggested that their socioeconomic status (e.g. education, income) affects their health more than other factors (De Gagne et al, 2014;De Gagne, Oh, So, Haidermota, & Lee, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the traditional role of a church as a religious institution, Korean churches in the USA play a fundamental role in the immigrant community by providing members with employment opportunities, fulfilling their psychosocial and cultural needs, as well as offering them health‐related information (De Gagne, Oh, So, & Kim, ). Korean immigrants who attend church often do so because of the opportunities to expand current social networks, and often view the congregation as an extended family (De Gagne et al ., ). Older Korean immigrants in the USA reported that those who actively participated in religious activities had a high level of life satisfaction and well‐being (Park et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations